Adsorption and separation of CO2/CH4 on binderless beads of 13X zeolite - Silva, José A.C. (2014)
The sorption equilibrium of CO2 and CH4 has been investigated on the binderless beads of 13X zeolite between 313 and 373 K and pressure up to 4 atm. The amount adsorbed of CO2 and CH4 is around 5.2 mmol/gads and 1.2 mmol/gads, respectively, at 313 K and 4 atm. Comparing these values with the ones in literature the value of CO2 is 20% higher than in similar 13X binder pellets.